Similarities between pyrrhonism and early buddhism - Medrano Arias, Daniel Ricardo (2024)
This essay examines the possible relationships that have been pointed out between Pyrrhonian skepticism and early Buddhism. After providing a brief historical overview of each philosophy, the results of the examination of the primary sources are presented in order to highlight the points of convergence and the differences found, offering more precise hypotheses about the similarities. Since it is feasible to consider interactions in both directions, the results of this initial exploration may be useful for scholars of Greek philosophy. Those engaged in reconstructing the history of Buddhism, and for contributing to the reflection on the links between East and West.